PEMBERIAN LATIHAN SENAM LOW IMPACT UNTUK MENINGKATKAN KESEHATAN REPRODUKSI BAGI MAHASISWI JURUSAN FISIOTERAPI POLTEKKES KEMENKES JAKARTA 3 - Ratu Karel Lina; Rovika Trioclarise; Ganesa Puput Dinda Kurniawan (IFI cabang Kota Bekasi, 2023)
Background: Primary dysmenorrhea is a physical disorder characterized by feelings of pain in women who are menstruating in the form of abdominal pain/cramps that are not caused by pathological conditions of the gynecological system. The cramps are mainly felt in the lower abdominal area and spread to the back or inner surface of the thighs. This pain usually disrupts the student's learning process. Several non-pharmacological treatments can reduce pain intensity. To reduce the intensity of primary dysmenorrhea pain, low impact aerobic exercise can be done for students in the second semester of the Health Polytechnic, Ministry of Health, Jakarta 3. Objective: providing training and assistance in implementing low impact gymnastics for female students. Method: In this program, several activities are carried out including: identification of personnel, facilities and infrastructure, training activities and assistance in implementing low impact exercise for female students. Results: This Community Service activity consists of providing demonstrations of low impact aerobic exercise and providing exercise assistance to respondents. This activity was carried out in September and October 2021 at the Poltekkes Kemenkes Jakarta 3. Conclusion: Community service activities in the form of demonstrations of low impact aerobic exercise and student mentoring activities were carried out well. Key words: low impact exercise, reproductive health